2018
DOI: 10.1002/eat.23000
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain trajectories during outpatient family‐based treatment for adolescents with anorexia nervosa

Abstract: Objective: Given that weight gain patterns in adolescents receiving outpatient Family-Based Treatment (FBT) have not been characterized, the purpose of this study was to examine trajectories of weight gain in a group of adolescent patients with a restrictive eating disorder [e.g., anorexia nervosa (AN) and atypical AN] receiving FBT. This study also examined the association of patient characteristics with weight gain trajectories, including age, diagnosis, weight suppression, presenting BMI-for-age percentile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Persons who experienced a cubic pattern of binge‐eating change (i.e., slow beginning, fast in the middle, and slow toward the end of treatment) reported fewer binge‐eating episodes at 6‐month follow‐up (Compare & Tasca, 2016). Similarly, persons with anorexia nervosa gained weight at different rates (Berona, Richmond, & Rienecke, 2018; Lebow et al, 2019; Makhzoumi et al, 2017). The rate of weight gain during treatment was indicative of treatment prognosis at discharge and follow‐up.…”
mentioning
confidence: 99%
“…Persons who experienced a cubic pattern of binge‐eating change (i.e., slow beginning, fast in the middle, and slow toward the end of treatment) reported fewer binge‐eating episodes at 6‐month follow‐up (Compare & Tasca, 2016). Similarly, persons with anorexia nervosa gained weight at different rates (Berona, Richmond, & Rienecke, 2018; Lebow et al, 2019; Makhzoumi et al, 2017). The rate of weight gain during treatment was indicative of treatment prognosis at discharge and follow‐up.…”
mentioning
confidence: 99%
“…It is possible that weight restoration to premorbid levels in AAN could further improve remission rates, but the authors' experience is that healthcare providers, patients, and families are reluctant to consider this option because of the medical risks associated with overweight and obesity. Another recent study on weight‐gain trajectories in FBT for adolescents with restricting eating disorders found that for AAN patients, the most common trajectory was an initial shallow slope of weight gain with a subsequent return to their pre‐intervention BMI and an overall weight maintenance at the 60th percentile throughout treatment (Lebow et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Latent class analysis such as GMM is increasingly being used to examine change during psychotherapy for ED and its relation to long‐term outcome. The number of distinct subgroups with differing trajectories of change vary from two (Presseller et al, 2022), three (de Vos et al, 2023; Espel‐Huynh et al, 2020; Hilbert et al, 2019; Makhzoumi et al, 2017), four (Austin et al, 2021; Melchior et al, 2016), to five classes (Castellini et al, 2013; Lebow et al, 2019; Montourcy et al, 2018). The studies followed patients during treatment, focusing on how distinct symptom profiles (Castellini et al, 2013; Montourcy et al, 2018) or different response patterns were related to outcome, finding that rapid response (Espel‐Huynh et al, 2020; Hilbert et al, 2019; Melchior et al, 2016) and early weight gain (Austin et al, 2021; Makhzoumi et al, 2017) were positive prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, long‐term outcome was limited to a timeframe of 3–18 months post‐treatment, except for a 6‐year follow‐up (Castellini et al, 2013) that used latent transition analyses and found moderate stability of profiles in a transdiagnostic sample of ED patients. Some studies only assessed limited parts of the ED psychopathology (Austin et al, 2021; Lebow et al, 2019; Makhzoumi et al, 2017), while others only included a single ED diagnosis (Hilbert et al, 2019; Makhzoumi et al, 2017) or assembled ED with other psychiatric disorders (Melchior et al, 2016; Montourcy et al, 2018). Moreover, these studies did not follow a naturalistic course over a longer time span or examine CM as a predictor of ED outcome.…”
Section: Introductionmentioning
confidence: 99%